Dietary exposure to environmentally relevant pesticide mixtures impairs swimming performance and lipid homeostatic gene expression in Juvenile Chinook salmon at elevated water temperatures. (1st December 2022) - Fuller, Neil; Magnuson, Jason T.; Huff Hartz, Kara E.; Whitledge, Gregory W.; Acuña, Shawn; McGruer, Victoria; Schlenk, Daniel; Lydy, Michael J.
Abstract: Aquatic organisms are exposed to complex mixtures of pesticides in the environment, but traditional risk assessment approaches typically only consider individual compounds. In conjunction with exposure to pesticide mixtures, global climate change is anticipated to alter thermal regimes of waterways, leading to potential co-exposure of biota to elevated temperatures and contaminants. Furthermore, most studies utilize aqueous exposures, whereas the dietary route of exposure may be more important for fish owing to the hydrophobicity of many pesticides. Consequently, the current study aimed to determine the effects of elevated temperatures and dietary pesticide mixtures on swimming performance and lipid metabolism of juvenile Chinook salmon, Oncorhynchus tshawytscha . Fish were fed pesticide-dosed pellets at three concentrations and three temperatures (11, 14 and 17 °C) for 14 days and swimming performance (Umax ) and expression of genes involved in lipid metabolism and energetics were assessed (ATP citrate lyase, fatty acid synthase, farnesoid x receptor and liver x receptor). The low-pesticide pellet treatment contained five pesticides, p, p'- DDE, bifenthrin, esfenvalerate, chlorpyrifos and fipronil at concentrations based on prey items collected from the Sacramento River (CA, USA) watershed, with the high-pesticide pellet treatment containing a six times higher dose. Temperature exacerbated effects of pesticide exposure on swimming performance, with significant reductions in Umax of 31 and 23% in the low and high-pesticide pellet groups relative to controls at 17 °C, but no significant differences in Umax among pesticide concentrations at 11 or 14 °C. At 14 °C there was a significant positive relationship between juvenile Chinook salmon pesticide body residues and expression of ATP citrate lyase and fatty acid synthase, but an inverse relationship and significant downregulation at 17 °C. These findings suggest that temperature may modulate effects of environmentally relevant pesticide exposure on salmon, and that pesticide-induced impairment of swimming performance may be exacerbated under future climate scenarios. Graphical abstract: Image 1 Highlights: Juvenile Chinook salmon dietarily exposed to pesticide mixtures at 11, 14 and 17 °C. Lower bioaccumulation of pesticides at 17 °C compared to 14 °C. Dysregulation of lipid homeostatic genes observed following pesticide exposure. Dietary pesticide mixtures reduced swimming performance at higher temperatures only. Temperature may exacerbate effects of environmentally relevant pesticide mixtures.